Literature Review−Effect of Additives and Post-Treatments on Corrosion Resistance and Mechanical Properties of Plasma Electrolytic Oxidation Products in Magnesium and Titanium - Sri Rahmadani; Anawati Anawati (Department of Physics, Sebelas Maret University, 2024)
Plasma Electrolytic Oxidation (PEO) is a method of converting metal surfaces into an oxide layer with the help of plasma to improve the surface mechanical properties and corrosion resistance of metals. A PEO layer of about 10-50 μm is obtained quickly from 1 second-10 minutes at a voltage range of 150-500 V with AC or DC mode. Characteristics of the outer layer of PEO have pores and cracks, while the inner layer is relatively denser. Cracks and pores reduce the corrosion resistance and mechanical properties of the coating. In this study, a literature search was carried out on the effect of adding additives and post-treatment on the characteristics of PEO coatings grown on magnesium (Mg) and titanium (Ti) metals for biomedical applications. Mg and Ti metals have opposite chemical properties; Mg is a reactive metal, while Ti is an inert metal. Comparing the behavior of the PEO process and the coating produced by the two different metals is absorbing and necessary to understand the fundamentals of the PEO process. The results of a literature search show that the addition of additives increases the growth rate of the coating so that the coating is thicker and more wear resistant. The hardness of the coating also increases due to the additive particles trapped in the oxide layer filling the micro pores so that the surface becomes denser and more homogeneous. Therefore, corrosion resistance also increases, as indicated by a decrease in corrosion current as measured by the polarization test and an increase in the impedance modulus as measured by the electrochemical impedance test (EIS). The post-alkali treatment allows for increased surface bioactivity, as indicated by the rise in the Ca/P ratio after immersion in a physiological solution.